A SWOT analysis on dispute resolution in the Islamic finance industry in Malaysia - Engku Ali, Engku Rabiah Adawiah; Oseni, Umar Aimhanosi; Abdul-Qadir Zubair, Aishat (2014)
As part of the transformation programme of the Malaysian government to make the country a sustainable global Islamic finance hub, the necessary legal and regulatory frameworks need to be put in place. While the regulatory authorities, such as Bank Negara Malaysia, have constantly introduced unprecedented reforms that are worth emulating in other jurisdictions, the challenge of adequate access to justice still lingers on despite the current diverse options available to the parties in Islamic banking issues. This paper therefore conducts a SWOT analysis on the effectiveness of the existing processes and legal institutions of dispute resolution specifically earmarked for Islamic finance matters. There is no doubt about the fact that the existing processes and institutions have their strengths; but they also have their weaknesses which can be addressed in the long run. The potential threats can be solved through proper implmentation of the existing legal and regulatory framework which presents a number of opportunities. The research concludes that since most Islamic financial institutions in Malaysia are more likely to use litigation for breach of contract; such attitude has relegated other sustainable processes of dispute resolution to the background and made them irrelevant in the Islamic finance industry. Hence, there is a need to consolidate the existing mechanisms in a more efficient manner that will benefit both the consumers and the Islamic financial institutions.